2022
DOI: 10.1029/2021ja030216
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on the Factors Controlling the Cusp Auroral Intensity Between the Northern and Southern Hemispheres

Abstract: The previous study has indicated that the interplanetary magnetic field (IMF) By and solar wind flow speed (Vsw) have crucial effects on the cusp auroral intensity in the Northern Hemisphere. However, it is not clear how these factors influence the cusp aurora in the Southern Hemisphere. Using DMSP/SUSSI observations from 2004 to 2017 during non‐storm periods, we compared the factors affecting the intensity of cusp aurora between the Northern and Southern Hemispheres by dividing the observations into weak‐ and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
(105 reference statements)
0
1
0
Order By: Relevance
“…11a and 13a). It has been shown that the B y component of the IMF can lead to interhemispheric asymmetries in the intensity of the aurora not only on the dayside (Qiu et al, 2022), but also on the nightside (Liou & Mitchell, 2019). Therefore, future work could explore to what extent these asymmetries can be found in auroral proton precipitation obtained with Vlasiator, should a 3D-3V run with a nonzero IMF B y become available.…”
Section: Limitations Of the Current Setupmentioning
confidence: 99%
“…11a and 13a). It has been shown that the B y component of the IMF can lead to interhemispheric asymmetries in the intensity of the aurora not only on the dayside (Qiu et al, 2022), but also on the nightside (Liou & Mitchell, 2019). Therefore, future work could explore to what extent these asymmetries can be found in auroral proton precipitation obtained with Vlasiator, should a 3D-3V run with a nonzero IMF B y become available.…”
Section: Limitations Of the Current Setupmentioning
confidence: 99%